SEISMIC ANALYSIS OF LIQUID STORAGE TANKS (Journal of Engineering, 2011)
earthquake excitations. Above and below ground tank, uses have been considered. A linear threedimensional finite element analysis has been used to predict the natural frequencies. Analysis parameters are the ratio of height to length of the tank, the type of soil, level of water in the tank, and also the wall thickness. The results for top displacement and axial force components for a full tankabove ground case have values greater than those in half- full (31%) and empty tank cases (75%). At the opposite of that, the underground tank demonstrates that top displacement and axial force components for an empty tank case have values greater than those in half- full (19%) and full tank cases (40%). The base shear for above ground tank case has values greater than those in underground tank cases (19% to 37%). The shear base for soil type 2 is greater than those in soil type 1(17% to 28%).